Imaging Human Breast Tumours in Different Species: How Human Are They? - Siegers, Gabrielle M.; Schueler, Julia; Leong, Hon Sing; Postovit, Lynne-Marie (Imaginations, 2020)
In a gedankenexperiment, we pose the philosophical question as to whether human breast cancer cells or tissues can still be considered human after transplantation into another species. Alongside medical research images illustrating xenotransplantation, we provide descriptions of how tissues were prepared for imaging. In addition, we discuss how such models enable further understanding of cancer and provide invaluable tools for testing new therapies.